PENGUJIAN FERTILITAS PATIN PASUPATI SECARA INTERNAL DAN EKSTERNAL MENGGUNAKAN PATIN SIAM Pangasianodon hypophthalmus (Sauvage, 1878) DAN PATIN JAMBAL Pangasius djambal Bleeker, 1846 - Evi Tahapari; Bambang Iswanto (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Pasupati is a pangasiid catfish resulted from hybridization between female striped pangasiid (Pangasianodon hypophthalmus) and male jambal (Pangasius djamba). Pasupati is known as a superior white-fleshy pangasiid catfish promoted for an export commodity. However, its reproductive characteristic in relation to its fertility has not been examined yet. The present study was conducted to investigate the successful of fertilization between female and male pasupati, reciprocal cross between pasupati with striped catfish, and reciprocal cross between pasupati with jambal catfish.Two to three females and males pasupati were used in the present study. All of breeders were hormonally induced for artificial. The result showed that there is no embryogenesis occurred when sperm from pasupati, striped and jambal catfish were used to fertilize eggs of pasupati catfish. On the other side, sperm enabled to fertilize eggs of striped cat fish producing low percentage of larvae with maternaly similar morphological appearances at juvenile stage. This phenomena showed that spontaneous gynogenesis occurred. In conclusion, female and male of pasupati cat fish are sterile.